Semantic And Scientific Differences Between Al-A’mā, Al-Akmah, And Ibyadhādh Al-‘Ain In The Qur’an Al-Karīm: الفروق اللغوية والعلمية بين الأعمى والأكمه وابيضاض العين في القرآن الكريم - Hanif, Imam Padhlurrahman; Aqdi Rofiq Asnawi; Rizky, Muhammad Sahil (ZAD Al-Mufassirin, 2024)
Blindness is a medical disease characterised by the partial or complete loss of vision, known as visual impairment or absolute blindness, respectively. The phenomenon of blindness is also mentioned in the Qur'an in several words, including: Al-A'maa, al-Akmah, and Ibyadhadh al-'Ain. This research intends to analyze the differences between al-A'maa, al-Akmah, and Ibyadhadh al-'Ain linguistically and scientifically. This study employs a library research methodology that utilises a descriptive and analytical technique to examine the linguistic and scientific distinctions among the three terms for blindness in the Qur'an. Several linguistic and scientific distinctions may be seen between the three terms of blindness that are found in the Qur'an, as shown by the findings of this research.: First, al-A'maa has two meanings, namely the ultimate meaning and majazi meaning. The connotation of the essential meaning of al-A'maa means total blindness, while the majazi meaning is related to disbelief and misguidance. Second, al-Akmah has three connotations of meanings: ophthalmic genetic, epiphora, and nyctalopia. Third, Ibyadhadh al-'Ain, which happened to the prophet Jacob As, is a cataract disease caused by traumatic and senile cataracts.